(untitled) (Research, Society and Development, 2021)
The rennet cheese produced in Northeastern Alagoas State is well known in Brazil. In addition, it is appreciated and consumed by the local population. Although this cheese type represents a segment of local economic importance, most of its production remains handcrafted, without proper technology using. The aim of the current study is to assess the microbiological quality of rennet cheese sold in supermarkets and street markets in Maceió (AL), in order to compare hygienic sanitary conditions between samples. A total of 24 samples rennet cheese samples were analyzed for total coliforms, as well as to investigate the incidence of coagulase-positive Staphylococcus and Salmonella sp. Results have suggested greater contamination with total coliforms and incidence of Salmonella sp. in artisanal rennet cheese samples. Larger number of cheese samples sold in supermarkets recorded positive results for coagulase-positive Staphylococcus. It was possible concluding that the herein analyzed rennet cheese samples did not meet the required microbiological quality standards. This outcome has indicated likely failure in production, transportation, storage and trading processes, which represents risks to human health.